2017
DOI: 10.1021/acs.jafc.7b02845
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Cork Extracts with (+)-Catechin and Malvidin-3-O-glucoside in Wine Model Solutions: Identification of a New Family of Ellagitannin-Derived Compounds (Corklins)

Abstract: The aim of this study was to evaluate the reactivity of phenolic compounds extracted from cork stoppers to wine model solutions with two major wine components, namely, (+)-catechin and malvidin-3-O-glucoside. Besides the formation of some compounds already described in the literature, these reactions also yielded a new family of ellagitannin-derived compounds, named herein as corklins. This new family of compounds that were found to result from the interaction between ellagitannins in alcoholic solutions and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Other types of compounds may be extracted from cork; these are various derivatives of terpenes, polyphenols, and others. There were recent reports about the reactivity of such extracts with compounds in wine (Azevedo et al., 2017) and a more comprehensive study using a metabolomic approach (Pinto et al., 2019), including NMR spectroscopy, to study the impact of the corks on wine.…”
Section: Status Quomentioning
confidence: 99%
“…Other types of compounds may be extracted from cork; these are various derivatives of terpenes, polyphenols, and others. There were recent reports about the reactivity of such extracts with compounds in wine (Azevedo et al., 2017) and a more comprehensive study using a metabolomic approach (Pinto et al., 2019), including NMR spectroscopy, to study the impact of the corks on wine.…”
Section: Status Quomentioning
confidence: 99%
“…Organic phases were combined, and the organic solvent evaporated in a speed vacuum [34]. The obtained fraction was then re-suspended in water/methanol (1/1; v/v) and analyzed by UPLC-DAD, using CH 3 COOH/H 2 O (1/99, v/v) and CH 3 COOH/CH 3 CN/H 2 O (1/20/79, v/v) as solvents [35]. Results were expressed as µg GAE.mg −1 dry weight.…”
Section: Reverse Phase Liquid Chromatography Analysis Of Polyphenolsmentioning
confidence: 99%
“…Polyphenols are easily extracted by a hydroalcoholic solution [55] and may react with the main components of wine [58], impacting on color and sensory properties of a bottled wine such as odor, flavor, and astringency. Azevedo et al [59] identified and quantified the phenolic compounds from cork that were able to migrate from different cork stoppers to wine model solutions during 27 months.…”
Section: Off-flavors and Beneficial Compoundsmentioning
confidence: 99%